KAPASITAS STRUKTUR KOLOM PIPIH BETON BERTULANG PADA PERUMAHAN VILLA ANGGREK KOTA PEKANBARU - Shanti Wahyuni Megasari; Gusneli Yanti; Zainuri (Jurnal Infrastruktur, 2020)
Renovation of structural buildings with additional levels of the building and changes in the function of the existing floors and strengthening of the existing columns can cause changes in the overall capacity of the building structure. Besides, the use of flat columns with the dimensions of the columns that are made flush with the walls will be better in terms of aesthetics, but the column must still be able to bear the load that works. So it is necessary to research the capacity of the flat column structure at Residential Villa Anggrek. Design and analysis of reinforced concrete building structures with the help of the ETABS v16.2.0, SAFE 16.0.1, and SPcolumn v.6.0 programs and then manually controlled based on SNI 03-2847-2013. In the implementation, 2 (two) calculations are carried out, namely on the existing structural elements and the plan structure. From the results of the analysis, it can be concluded that the capacity of the existing and planned structures that use the reinforced concrete flat column structure at the Residential Villa Anggrek, Pekanbaru City is safe to accept the load combination according to SNI 2847-2013. As well as the use of flat columns with the dimensions of the column made flat against the walls so that it will be better in terms of aesthetics but still able to bear the workload. As well as the use of flat columns with the dimensions of the column made flat against the walls so that it will be better in terms of aesthetics but still able to bear the workload.